Pengaruh Bauran Pemasaran 7P Terhadap Loyalitas Konsumen Produk Olahan Kopi Gincu di Kota Cirebon - Winata, Tina Pandu; Budiraharjo, Kustopo; Nurfadillah, Suryani (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The study aimed to identify consumer characteristics of processed Kopi Gincu products, analyze the 7P marketing mix and consumer loyalty and its influence on processed Kopi Gincu products in Cirebon City. The research was conducted in December 2022 - February 2023. The location of the research was at Kopi Gincu which is located in Sedong Lor Village, Sedong District, Cirebon City. The study used a survey method with accidental sampling technique. The results showed that the majority of consumers were male, aged 18-25 years, the average consumer was still a student, domiciled from Cirebon City, had a monthly income ranging from less than Rp. 500,000, the number of purchases that were made for one time coming and consuming Gincu Coffee was Rp. 25,001 to Rp. 75,000. The majority of consumers visit Kopi Gincu together with their friends (school friends, college friends or work friends) and the majority know information about the place/location of Kopi Gincu from social media and also recommendations from other people (friends, girlfriends or family). Descriptively, the 7P marketing mix and also consumer loyalty at Kopi Gincu are only perceived as quite good because they are classified in the medium category. Product, price, promotion, place, people, process, and physical evidence variables simultaneously affect consumer loyalty for processed Kopi Gincu products in Cirebon City. However, partially only 4 variables have an effect on consumer loyalty, namely price, place, process, and physical evidence. Marketing mix variables product, price, promotion, place, people, process, and Physical Evidence are able to explain variations in changes in consumer loyalty variables by 79.3%. While the remaining 20.7% is explained by other variables outside the model.